(untitled) (Thailand, 1996)
Achieving this goal is a long-term process that will require confidence building amon industry, regulators, and public, the nurturing, the development of common approaches to characterrize and manage environmental changllenges, a comparative assessment of regional environmental laws and requlations and finally th implementation of an effective process for drating legislation and administrative decrees for oil and gas regulation
Keywords: Petroleum industry and trade,Gas industry,Environmental protection; Government policy,Chính sách của chính phủ; Thương mại vàcông nghiệp dầu mỏ; Vietnam